Corruption, natural resources and development: from resource curse to political ecology - Boamah, Festus (Edward Elgar Publishing, 2017)
"'Corruption, Natural Resources and Development' provides a fresh and extensive discussion of corruption issues in natural resources sectors. Reflecting on recent debates in corruption research and revisiting resource curse challenges in light of political ecology approaches, this volume provides a series of nuanced and policy-relevant case studies analysing patterns of corruption around natural resources and options to reach anti-corruption goals. Using corruption case studies across a wide spectrum of natural resource sectors from around the world, the expert contributions explore political ecology as a means of analysing resource curse challenges. The potential for new variations of the resource curse in the forest and urban land sectors and the effectiveness of anti-corruption policies in resource sectors are considered in depth. Corruption in oil, gas, mining, fisheries, biofuel, wildlife, forestry and urban land are all covered, and potential solutions discussed. This forward-thinking book is essential reading for students and academics in the fields of development studies, political ecology, corruption, development economics and international political economy. The evidence and policy solutions included will be of great appeal to policymakers and practitioners." - Provided by publisher